The thermal annealing effect on Crystal Structure and Morphology of Titanium Dioxide (TiO2) powder - Edy Supriyanto; Ashanal Holikin; Suwardiyanto Suwardiyanto (Jurnal ILMU DASAR, 2014)
In this research, crystal structure and morphology of TiO2 (powder) has been observed. TiO2 (powder) was heated by furnace unit at temperature 200 °C - 400 °C to obtain the relation of temperature influences to crystallty and morphology of TiO2. Structural characterization has been done using XRD whereas morphology using Scanning Electron Microscope (SEM) method. The result of this research showed that form of the TIO2 structure was polycrystalline in which mostly dominated by crystal structure (101). Scherrer method used to obtain information that at temperature 300oC, TiO2 has a real small particle size less than 10 nm and large pore size to serve the purpose of photocatalyst material. Keywords : Crystal structure,crystalline size, photocatalyst, morphology, SEM, TiO2.